2022
DOI: 10.1186/s40468-022-00176-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of classroom-based feedback on speaking assessment: a multifaceted Rasch analysis

Abstract: Due to subjectivity in oral assessment, much concentration has been put on obtaining a satisfactory measure of consistency among raters. However, the process for obtaining more consistency might not result in valid decisions. One matter that is at the core of both reliability and validity in oral assessment is rater training. Recently, multifaceted Rasch measurement (MFRM) has been adopted to address the problem of rater bias and inconsistency in scoring; however, no research has incorporated the facets of tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Additionally, students' self-concept, self-identity, and sociocultural background are critical in the depth of students' attitudes toward CSA (Bourke & Mentis, 2007, 2013. As the previous studies pinpointed, investment in boosting CSA strategies among EFL learners influenced their academic well-being (Bijani et al, 2022;Heydarnejad, Ismail, et al, 2022;Punpromthada et al, 2022). According to Al-Mamoory and Abathar Witwit (2021), the more learners practice CSA, the better they can decide reflectively.…”
Section: The Core Of Self-assessment (Csa)mentioning
confidence: 96%
“…Additionally, students' self-concept, self-identity, and sociocultural background are critical in the depth of students' attitudes toward CSA (Bourke & Mentis, 2007, 2013. As the previous studies pinpointed, investment in boosting CSA strategies among EFL learners influenced their academic well-being (Bijani et al, 2022;Heydarnejad, Ismail, et al, 2022;Punpromthada et al, 2022). According to Al-Mamoory and Abathar Witwit (2021), the more learners practice CSA, the better they can decide reflectively.…”
Section: The Core Of Self-assessment (Csa)mentioning
confidence: 96%
“…Shafiee Rad and Jafarpour (2022) affirmed that EFL students’ affection control and L2 grit impact their flexibility. Siemer (2001) and Bijani et al (2022) demonstrated the importance of self-assessment in EFL teachers’ self-efficacy. Peistaraite and Clark (2020) discovered that emotion planning promotes self-organized learning in classical musicians.…”
Section: Discussionmentioning
confidence: 99%
“…From a different angle, Essau (2021) defined emotions as personally constructed states of being that can result from conscious evaluations of personal accomplishments in achieving objectives or upholding standards or beliefs during interactions within social-historical contexts. The process-oriented model of ER typically defines the techniques used in affection control (Aunola et al, 2015; Bijani et al, 2022). This paradigm categorizes affection control into five groups: context selection, situation alteration, attentional focus, cognitive shift, and response modulation.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%